(untitled) (Research, Society and Development, 2020)
The study aims to analyze the prevalence and factors associated with the presence of the First Contact Access attribute in Primary Health Care services in the municipalities belonging to the 4th Regional Health Coordination. This is a multilevel observational cross-sectional study on two levels: individual (health professionals) and contextual (municipalities), carried out with health professionals at a higher level, in the Primary Health Care services of the municipalities belonging to the 4th Regional Health Coordination Individual data were collected using a socio-economic questionnaire and the Primary Care Assessment Tool-Brasil version professionals. Contextual data on official websites of the Brazilian Federal Government. There were no individual variables with statistical significance in the presence of the First Contact Access attribute. Among the contextual ones, only the population size was shown to be statistically significant for the presence of the attribute, with municipalities with up to five thousand inhabitants having the highest prevalence of this attribute in Primary Health Care. The results found show that the factor associated with the presence of First Contact Access in Primary Health Care that showed statistical significance for its prevalence was the small population size of the cities surveyed. This shows that municipalities with a smaller population have better access to this level of care. This study contributes to the knowledge about the theme, since it makes it possible to identify the context that most influences the prevalence of First Contact Access, contributing to direct the aspect to be explored in new studies. In order to recognize that there are still barriers of access to be overcome in order to guarantee the effectiveness of Primary Health Care.